The Position of Maqasid al-Shariah within Islamic Legal Sources: A Comprehensive Analysis - Alias, Muhammad Nazir; Abdullah, Muhammad Najib; Osman, Mohd Farihal; Ismail, Nor Faizah; Kamis, Mohd Sham (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study examines the position of maqasid al-shariah (objectives of Islamic law) within the hierarchy of Islamic legal sources and its role in contemporary legal derivation. While maqasid al-shariah serves as a framework for preserving five essential elements (religion, life, intellect, lineage and property), its precise position within Islamic legal sources remains ambiguous. This research addresses whether maqasid functions as a primary source equivalent to the Quran and Sunnah or merely as an interpretative tool and how it interacts with secondary sources like qiyas, istihsan and maslahah mursalah. Employing document analysis, comparative analysis and interdisciplinary approaches integrating usul al-fiqh and maqasid studies, this research examines primary Islamic sources and classical and contemporary scholarly works. Findings reveal that maqasid maintains an organic relationship with primary sources while serving as an evaluative framework for secondary sources. In qiyas, maqasid guides identification of 'illah (legal cause); in istihsan, it justifies departures from strict analogical reasoning; for maslahah mursalah, it distinguishes valid public interests; and it filters ‘urf (custom) and guides sadd al-dhara'i (blocking means to harm). Contemporary applications in Malaysia and Indonesia demonstrate maqasid's practical significance. During COVID-19, religious authorities used maqasid-based reasoning to suspend congregational prayers, prioritizing life preservation. In Islamic finance, maqasid principles guide evaluation of cryptocurrency and digital sukuk. The emergence of “maqasid-oriented ijtihad” represents a methodological innovation integrating traditional usul al-fiqh with maqasid considerations. This research clarifies that maqasid al-shariah functions not as a separate hierarchical source but as an integral framework permeating all levels of legal derivation. The findings suggest traditional usul al-fiqh methodologies, when properly integrated with maqasid principles, remain adequate for realizing shariah objectives in modern contexts, though requiring dynamic application responsive to contemporary realities.